PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN KONSUMEN, DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN PENGGUNA JASA GOJEK DI KABUPATEN GIANYAR - I Putu Kevin Gautama; I Wayan Widnyana; I Wayan Sukadana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
The development of information technology in the era of modernization or the 5.0 era is increasing day by day to become more sophisticated. The number of social media users in the world, especially in Indonesia, is also increasing. With the number of technology users in the world, it is used as best as possible by companies around the world. The increased mobility of the public in an open environment (outdoor) opens up opportunities for service providers, especially transportation services, to utilize social media as a means of distribution. One of them is Gojek. For the last 3 years, Gojek has always been ranked first in the Top Brand Index of the Indonesian Category, an online transportation service provider. There must be factors that influence Gojek to always rank at the top of Indonesia's Top Brand Index for the category of online transportation service providers. Therefore, this study aims to determine the effect of service quality, consumer trust, and brand image on the loyalty of Gojek service users in Gianyar Regency. This research was conducted in Gianyar Regency. The method of data collection was through distributing questionnaires to 126 respondents who were Gojek users who had used Gojek services at least 2 times and lived in the Gianyar area. The analytical techniques used in this study are Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Korelasi Analysis, Determination Test (R2), Hypothesis Testing which is processed using the IBM SPSS 25.0 application for Windows. The results of the analysis show that 1) service quality has a positive and significant effect on customer loyalty for Gojek service users, 2) consumer trust has a positive and significant effect on customer loyalty for Gojek service users, 3) brand image has a positive and significant effect on customer loyalty for Gojek service users.